Unionization and Profitability in the Canadian Manufacturing Sector - Laporta, Pasquale; Jenkins, Alexander (Relations industrielles / Industrial Relations, 1996)
This study looks at the effects of unions on profitability in the Canadian manufacturing sector, taking into account structural factors such as concentration and entry barriers. The authors find that, although there is a moderately positive relationship between unionization and profitability at low tevels of concentration, at higher levels of concentration unions are able to extract an increasing proportion of incrémental profits that the firm (industry) may earn, until any incrémental profit (rent) associated with further increases in industry concentration is completely captured by the union. This may reflect a greater ability on the part of unions to organize and exercise bargaining power in concentrated industries and redistribute income from capital to labour, but it also leads to underproduction and resource misallocation.